Efektivitas Model Pembelajaran Numbered Heads Together (NHT) Berbasis Gamifikasi Roda Putar dalam Meningkatkan Hasil Belajar Trigonometri Siswa - Siti Maysaroh; Moh. Abdul Qohar (PT Cendekia Education Center, 2026)
This study aims to determine the effectiveness of the Numbered Heads Together (NHT) learning model based on spinning wheel gamification in improving trigonometry learning outcomes of class X students of MA Al-Amiriyyah Blokagung Banyuwangi. This study uses a quantitative approach with a quasi-experimental research type and a pretest-posttest control group design. The research sample consists of two classes, namely the experimental class that received learning using the NHT model based on spinning wheel gamification and the control class that received conventional learning. The data collection technique used learning outcome tests in the form of pretest and posttest. Data analysis was carried out through normality tests, hypothesis tests using the Wilcoxon Signed-Rank Test and Mann-Whitney U Test, and N-Gain analysis to determine the improvement in student learning outcomes. The results showed that the average pretest and posttest scores of the experimental class increased from 64.67 to 88.67, while the control class increased from 63.26 to 75.43. The Wilcoxon test results showed a significance value of 0.000 < 0.05 and the Mann-Whitney test results showed a significance value of 0.000 < 0.05, which means there is a significant difference in learning outcomes between the experimental class and the control class. In addition, the average N-Gain value of the experimental class was 65.54%, which is included in the fairly effective category, while the control class was 30.90%, which is included in the ineffective category. Thus, the Numbered Heads Together (NHT) learning model based on spinning wheel gamification is effective in improving students' trigonometry learning outcomes.